2021
DOI: 10.1111/myc.13297
|View full text |Cite
|
Sign up to set email alerts
|

Fungaemia due to rare yeasts in paediatric intensive care units: A prospective study

Abstract: Fungaemia due to yeast is a major cause of morbidity, mortality and increased healthcare costs in critically ill patients in intensive care units (ICUs). [1][2][3][4] The overuse of antibiotics, multiple invasive procedures and compromise in infection control contribute to the rise of fungaemia in ICUs. 2 While majority of the epidemiological studies covered adult patients in ICUs, the limited studies in paediatric ICUs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…According to the 22 publications of C. auris infection, comprising 256 children [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], reviewed herein, the most common type of invasive infection was bloodstream infection (94%, 194/206 patients with available data on the infection site) ( Table 3 and Table S1 ). The duration of candidemia was not reported in most studies and was available for only seven patients; the duration ranged between 7 and 11 days [ 16 , 20 , 36 ].…”
Section: Clinical Spectrum Of C Auris Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the 22 publications of C. auris infection, comprising 256 children [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], reviewed herein, the most common type of invasive infection was bloodstream infection (94%, 194/206 patients with available data on the infection site) ( Table 3 and Table S1 ). The duration of candidemia was not reported in most studies and was available for only seven patients; the duration ranged between 7 and 11 days [ 16 , 20 , 36 ].…”
Section: Clinical Spectrum Of C Auris Infectionmentioning
confidence: 99%
“…Publications were reviewed and selected based on their quality and pertinence. Following exclusion of suspected repetitive studies, the search yielded 23 publications that reported C. auris incidents in children [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Twelve publications included both adult and pediatric patients [ 17 , 19 , 20 , 23 , 24 , 26 , 27 , 28 , 32 , 35 , 36 , 37 ]; of them, one did not provide specific details of the pediatric patients and was excluded [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were seven residents colonized by C. pararugosa , which was first reported in 2017 to cause bloodstream infections [ 27 ]. Hence, it is worth noting that in addition to those common species that cause diseases in humans, some rare species that were recovered in the present study such as Candida norvegensis [ 28 ], C. utilis [ 29 ], Cystobasidium minutum ( Rhodotorula minute ) [ 30 ], Exophiala dermatitidis [ 31 , 32 , 33 ], Lodderomyces elongisporus [ 34 , 35 ], Magnusiomyces capitatus [ 36 ], and Trichosporon mucoides [ 37 ] have been reported to cause invasive infections in humans.…”
Section: Discussionmentioning
confidence: 99%
“…He recovered after fluconazole therapy. Kaur et al (2021) performed a systematic epidemiologic study on fungaemia caused by rare yeasts, and from a total of 127 isolates, 43 were identified as W. anomalous. Perez-Traves et al (2021) investigated factors potentially related to virulence and pathogenicity in a Galleria mellonella model for a collection of clinical and food/environmental isolates of D. hansenii, K. marxianus and W. anomalous.…”
Section: Wickerhamomyces Anomalusmentioning
confidence: 99%